2004
DOI: 10.2165/00019053-200422010-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentre Study of Patient Survival, Disability, Quality of Life and Cost of Care

Abstract: This is the first study to present a comprehensive comparison of direct costs, DD and HR-QOL of patients with AIDS between two time periods. The use of a case-control design has enabled changes in costs and outcomes to be linked to the introduction of HAART in Italy in 1997.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
0
24
0
2
Order By: Relevance
“…As efforts to improve access to HIV treatment in resource-limited areas such as sub-Saharan Africa increase [5], strategies to manage the adverse effects of BFR on QoL become more crucial, as these management strategies may enhance treatment adherence [6]. Measures of QoL provide valuable information about patients' well being, psychological and social functioning, and the cost-effectiveness of intervention trials [7]. Therefore, there is a need to test and identify effective interventions that may alleviate the psychological and social consequences of HAART-and HIV-related BFR and enhance QoL of HIV+ patients receiving HAART.…”
Section: Introductionmentioning
confidence: 99%
“…As efforts to improve access to HIV treatment in resource-limited areas such as sub-Saharan Africa increase [5], strategies to manage the adverse effects of BFR on QoL become more crucial, as these management strategies may enhance treatment adherence [6]. Measures of QoL provide valuable information about patients' well being, psychological and social functioning, and the cost-effectiveness of intervention trials [7]. Therefore, there is a need to test and identify effective interventions that may alleviate the psychological and social consequences of HAART-and HIV-related BFR and enhance QoL of HIV+ patients receiving HAART.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The proportion of medical costs attributable to antiretroviral therapy in our study (61%) was also similar to that found in previous studies. [1,4,8] The association of baseline CD4+ cell count with cost of medical care has been previously demonstrated. [1] Age as a factor associated with increased total medical costs is not surprising as it likely acted as a surrogate for increased co-morbid illness.…”
Section: Discussionmentioning
confidence: 91%
“…[5] After the introduction of potent combination antiretroviral therapy, the need for hospitalization and the incidence of opportunistic illness decreased considerably. [6][7][8] It is now estimated that 54−64% of healthcare expenditures in HIV-infected populations in resourcerich settings are attributed to the cost of combination antiretroviral therapy. [1,4,8] Despite the expense, antiretroviral therapy is cost effective for HIV-infected individuals in resource-rich (and resource-limited) settings.…”
Section: Background and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study that retrospectively compared data of a cohort of symptomatic patients in 1994 with a similar cohort in 1998, a reduction of 3925 euro (1999 prices) in direct health costs per person-year was calculated. In 1998, ART costs per patient-year were equal to 7283 euro and accounted for 63.5% of total direct medical costs [20].…”
Section: Discussionmentioning
confidence: 99%